SURGERY RESULTS OF CANCER OF THE WOMB (UTERUS) AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Background: Surgical treatment is an important method, applied to early stage uterine cancerpatients.Objective: To evaluate the results of surgery for uterine cancer at Nghe An Obstetrics andPediatrics Hospital.Methods: Retrospective and prospective cross-sectional description of 49 patients diagnosedwith uterine cancer at Nghe An Obstetrics and Children's Hospital from June 2020 to June 2022.Result: The average age of patients at the time of diagnosis was: 68 years old. Cervical canceraccounted for 79.6%, endometrial cancer accounted for 20.4%. The value of magnetic resonancein assessing and classifying uterine cancer stage: stage I is 83.3%, stage II is 85.7%, the total ofboth stages is 84.2%. Compared with the laparotomy method, laparoscopic surgery has manyadvantages: lower complication rate, shorter postoperative transit time, less blood loss, lowerpatient lower blood transfusion.Conclusion: Radical surgery at the beginning is indicated for FIGO stage I and II uterine cancerwith good, safe treatment results and complications within acceptable limits.
Keywords: Uterine cancer, surgery.